第二个疑问,。。。。

$\lim\limits_{x \to 0}$$\cfrac{f(2x)-f(x)}{x}$$=A$,说明$f(2x)-f(x)$$=Ax+0(x)$,x$\to$0 (1)
根据(1)式,得到 $f(x)-f(\cfrac{x}{2})$$=A\cfrac{x}{2}+0(\cfrac{x}{2})$, x$\to$0
$f(\cfrac{x}{2})-f(\cfrac{x}{({2})^{2}})$$=A\cfrac{x}{({2})^{2}}+0(\cfrac{x}{({2})^{2}})$ x$\to$0
..............
$f(\cfrac{x}{({2})^{k-1}})-f(\cfrac{x}{({2})^{k}})$$=A\cfrac{x}{({2})^{k}}+0(\cfrac{x}{({2})^{k}})$,x$\to$0
然后再把上面$k$个等式相加即可得到 $f(x)-f(\cfrac{x}{({2})^{k}})$$=Ax\sum_{i=1}^{k}\cfrac{1}{({2})^{i}}+\sum_{i=1}^{k}0(\cfrac{x}{({2})^{i}})$,x$\to$0
当k$\to$$\infty$时 ,就得到了$f(x)-f(0)$$=Ax+0(x)$,x$\to$0 从而得到了$f'(0)=A$ 证毕。
已邀请:

要回复问题请先登录注册